Hubungan Dukungan Sosial Dengan Problem Solving Keluarga Yang Merawat Penderita Stroke Dalam Kesembuhan Pasien - Elvira Mustika Watie; Anik Suwarni; Indriyati Indriyati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Stroke is one of the non-communicable diseases with the highest mortality and disability rates in Indonesia and the world. The role of the family in the process of caring for stroke patients is very important, especially in providing social support and problem solving skills during the recovery period. Social support includes emotional, informational, and instrumental aspects that can affect the mental and physical health of patients and families who care for them. Family problem solving skills are also key in overcoming various challenges in caring for stroke patients who require intensive attention and assistance.This study aims to analyze the relationship between social support and family problem solving skills in caring for stroke patients and its relationship to the patient's recovery process. This study uses a quantitative approach with a correlational analytical research type and a cross-sectional research design. Sample selection uses the Purposive Sampling technique. Data analysis uses the Kendall Tau correlation test.There is a relationship between social support and problem solving of families caring for stroke patients in patient recovery with a significance value of 0.019 <0.05, which means that there is a significant relationship between social support and problem solving. Then, from the Correlation Coefficient, the closeness of the relationship and the direction of the relationship can be seen, the Correlation Coefficient value shows a result of 0.31 which is a positive number.The higher the social support obtained by families caring for stroke patients, the higher the level of problem solving they have.